New Δ-tocotrienol derivatives from Colombian propolis - Popova, Milena P.; Trusheva, Boryana S.; Nedialkov, Paraskev T.; Tsvetkova, Iva; Pardo-Mora, Dolly P.; Najdenski, Hristo; Torres-García, Orlando A.; Sforcin, José M. [UNESP]; Bankova, Vassya S. (Taylor & Francis, 2019)
Two new δ-tocotrienol derivatives with oxidized terminal chain: 5,6-dioxo-garcinoic acid (trans-13′-carboxy-5,6-dioxo-δ-tocotrienol) (2) and 5-hydroxy-8b-oxo garcinoic acid (trans-13′-carboxy-5-hydroxy-8b-oxo-δ-tocotrienol) (3), together with one known derivative garcinoic acid (trans-13′-carboxy-δ-tocotrienol) (1) were isolated from a Colombian propolis. Garcinoic acid was found as a propolis constituent for the first time. The isolated compounds and crude ethanolic extract demonstrated high antimicrobial activity against Staphylococcus aureus and Candida albicans (MICs range: 10–39 μg/ml) as well as promising antioxidant potential in DPPH assay. Compound 3 displayed highest radical scavenging activity, even higher than that of dl-α-tocopherol, used as a positive control.
Keywords: antimicrobial activity; DPPH scavenging activity; garcinoic acid; Propolis; δ-tocotrienol derivatives